Expans\~ao da produç\~ao agrícola, novas tecnologias de produç\~ao, aumento de produtividade e o desnível tecnológico no meio rural - Caroline Nascimento Pereira; César Nunes De Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
The growing demand for food and energy, in the face of population growth, is an increasingly present theme in debates about agriculture. In the last century, innovations were fundamental to achieve population growth, such as the Green Revolution and its importance for the introduction of large-scale agriculture in the interior of Brazil, making the country a food exporter. The concern with increased consumption persists, added to concerns about the climate and desertification of areas around the world, which imposes a new wave of innovations and solutions to achieve present and future demand. Digital agriculture, or also known as Agriculture 4.0, has been pointed out as a possible solution to the current and future problems of the sector, based on precision agriculture and new technologies, saving resources, reducing costs and increasing productivity. However, new technologies are not accessible to all farmers, as most of these technologies depend on internet infrastructure, which is still precarious in much of Brazil, in addition to having an access cost that is often unfeasible for small producers.
Keywords: Q10; Q11; Q16; 330; crop projections; innovation; Agriculture 4.0; small farmer